2020
DOI: 10.1016/j.resinv.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of early-stage combination treatment with favipiravir and methylprednisolone for severe COVID-19 pneumonia: A report of 11 cases

Abstract: Although the use of corticosteroids is not recommended in the World Health Organization statement for the treatment of coronavirus disease 2019 (COVID-19), steroid therapy may be indicated for critical cases in specific situations. Here, we report the successful treatment of 11 cases of severe COVID-19 pneumonia with favipiravir and methylprednisolone. All cases were severe and patients required oxygen administration or had a blood oxygen saturation ≤93% on room air. All were treated with favipiravir and methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…As of December 2020, the numbers of patients with COVID-19 and associated deaths are still rapidly increasing. Some existing drugs have been reported to be effective in patients with COVID-19 [ 1 , 2 , 3 ]. However, many patients with COVID-19 become severe or critical despite treatment with antiviral or anti-inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…As of December 2020, the numbers of patients with COVID-19 and associated deaths are still rapidly increasing. Some existing drugs have been reported to be effective in patients with COVID-19 [ 1 , 2 , 3 ]. However, many patients with COVID-19 become severe or critical despite treatment with antiviral or anti-inflammatory drugs.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the use of dexamethasone in patients hospitalized with COVID-19 resulted in a lower 28-day mortality among those who were receiving either invasive mechanical ventilation or oxygen alone ( 6 ). We recently reported that the combined treatment of mPSL and favipiravir during the early stage of infection in patients with severe COVID-19 pneumonia may prevent aggravation ( 15 ), as seen in this case. We also used ciclesonide and nafamostat mesylate to anticipate an anti-viral effect and intravenous immunoglobulin to anticipate dual effects of immune substitution and immunomodulation.…”
Section: Discussionmentioning
confidence: 52%
“…Authors conclude that in their pilot study, favipiravir appeared beneficious among moderately ill patients [16]. In small case series studies, favipiravir was administered with nafamostat mesylate or methylprednisolone for COVID-19 patients in different disease stages, but due to the lack of control groups and antiviral combination usage, the extent favipiravir effect on clinical cure remains ambiguous [17-19]. In all, we think that our findings could be reflected by data from current literature, and the role for favipiravir should not be overestimated in the treatment of adults with moderate to severe COVID-19.…”
Section: Discussionmentioning
confidence: 99%